(untitled) (American Journal of Islam and Society, 2013)
Narrating the history of a nation from approximately 1,000,000 BCE to 2009 CE in 389 pages is a daunting and noteworthy task undertaken by the scholars who have contributed to The Oxford Handbook of Iranian History. This collection of sixteen short essays by distinguished anthropologists, archaeologists, historians, and philologists of the Iranian world divides Iranian history into three general periods: ancient, medieval, and modern. Chapters 1 to 7 address the ancient Iranian dynasties, chapters 8 to 13 talk about medieval Iran, and the last three focus on modern Iran. In the words of editor Touraj Daryaee, each chapter has been written in a way to provide “comprehensive information for students at the university level and for the uneducated layperson” (p. ii). Therefore, the book is intended to be more of an introduction rather than a reference book for scholarly research ...